Computational Analytical Methods for Buildings and Cities: Space Syntax and Shape Grammar - Ostwald, Michael J.; Lee, Ju Hyun (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue presents computational techniques used to examine the social, spatial, and functional characteristics of buildings and cities. Focused on two renowned computational methods in architectural and urban analytics-Shape Grammar and Space Syntax-this reprint demystifies the 'grammar', 'syntax', and 'style' of space and form. These properties are used to understand the fabric of built environments, and their underlying tendencies, social patterns, and potentials. With these articles, this Special Issue serves as a compass for architects, urban planners, researchers, and students navigating architectural and urban designs. Each contribution emphasizes the fundamental principles of design analysis or generation, offering insights into a range of topics, such as historic architecture, spatial genotypes and configurations, agent-based modelling, and urban landmarks. The readers of this volume will improve their understanding of the planning and optimization of built environments, as well as the creation of future cities.